Institusi Pemerintah dan Sistem Pengelolaan Dalam Membangun Good Governance - Ayu, Ayu Restianti; Subaidi, Subaidi (UIR Press, 2024)
This research aims to analyze the condition of public services in Indonesia and describe digital-based pilot public services in Pleret Kapanewon Pleret District, Bantul Regency, Yogyakarta Special Region Province (DIY) in order to create government institutions and management systems in building good governance. This research method uses literature review. Data obtained from the Daily Analysis Opinion column, January 25 2023 Edition published by PT. Media Warta Kencana entitled